Comparison of Comminuted Femoral Shaft Fracture Treatment between Locking Compression Plate and Conventional Dynamic Compression Plate Methods: A historical control an interventional study - Amornmoragot, MD, Tawatchai (Journal of Southeast Asian Orthopaedics, 2022)
Background: The standard treatment for comminuted femoral shaft fracture is intramedullary nailing. However, an alternative treatment where intramedullary nailing is contraindicated, plating can be performed using either a conventional dynamic compression plate (DCP) or a locking compression plate (LCP). Objective: To compare results of comminuted femoral shaft fracture treatment with locking compression plate and with conventional dynamic compression plate methods. Materials and Methods: A group of 40 patients admitted to Roi Et Hospital in northeastern Thailand between January 2016 and December 2018 were divided equally into 2 groups. The first group was operated on using the conventional dynamic compression plate method; the locking compression plate method was used with the second group. The study compared the rate of bone union (time to healing) and postoperative complications with the two methods. Design: Historical control interventional study. Results: In both DCP and LCP technique average healing rate were 20 weeks. However, more postoperative complications were found with the dynamic compression plate method, e.g., a broken plate was found occurred in 5 patients and malunion was discovered in 2 patients, while the group treated with the locking compression plate method had no broken plates and only one patient with malunion. Conclusions: The locking compression plate method is appropriate for comminuted femoral shaft fracture treatment as it provides a better rate of bone union (healing rate) and fewer postoperative complications than the conventional dynamic compression plate method.